Leuconostoc mesenteroides mediates an electrogenic pathway to attenuate the accumulation of abdominal fat mass induced by high fat diet - Minh Tan Pham (Nature Portfolio, 2020)
Abstract Although several electrogenic bacteria have been identified, the physiological effect of electricity generated by bacteria on host health remains elusive. We found that probiotic Leuconostoc mesenteroides (L. mesenteroides) can metabolize linoleic acid to yield electricity via an intracellular cyclophilin A-dependent pathway. Inhibition of cyclophilin A significantly abolished bacterial electricity and lowered the adhesion of L. mesenteroides to the human gut epithelial cell line. Butyrate from L. mesenteroides in the presence of linoleic acid were detectable and mediated free fatty acid receptor 2 (Ffar2) to reduce the lipid contents in differentiating 3T3-L1 adipocytes. Oral administration of L. mesenteroides plus linoleic acid remarkably reduced high-fat-diet (HFD)-induced formation of 4-hydroxy-2-nonenal (4-HNE), a reactive oxygen species (ROS) biomarker, and decreased abdominal fat mass in mice. The reduction of 4-HNE and abdominal fat mass was reversed when cyclophilin A inhibitor-pretreated bacteria were administered to mice. Our studies present a novel mechanism of reducing abdominal fat mass by electrogenic L. mesenteroides which may yield electrons to enhance colonization and sustain high amounts of butyrate to limit ROS during adipocyte differentiation.